Firepower 2030 - Chakravorty, P. K. (2013)
Warfare quintessentially comprises Firepower and Manoeuvre. Terrain and the nuclear overhang restrict manoeuvre in our theatre of operations.The constituents of Firepower are platforms with ammunition, which can deliver from five dimensions; Land, Air, Surface of the sea, below the surface of the sea and possibly in times to come Outer Space. These are Small Arms, Guns, Mortars, Rockets of Artillery, Tanks, Aircrafts, Missiles, Unmanned Combat Aerial Vehicles (UCAVs), Armed Helicopters, Submarines and in future possibly stations in Outer Space. The ammunition which is the payload is the most important element of Firepower. Combination of platforms with ammunition results in devastating Firepower which paves the way for victory. The constituents enable us in a full spectrum conflict to undertake net centric operations. The conflicts visualised could be Land operations in a Counter Insurgency situation against non state actors, Air Land operations in a counter insurgency operation or a conventional conflict, Air operations for Counter Air, Air Defence, Sea operations for sea control or denial, Sea Land operations to undertake Amphibious operations, Air Sea operations between two opposing naval task forces and possibly by 2030 operations involving Outer Space. In these conflicts victory would be attained by ensuring Asymmetries of Firepower.